Amputations for extremity soft tissue sarcoma in an era of limb salvage treatment: Local control and survival. Issue 3 (16th October 2017) - Stevenson, Marc G.; Musters, Annelie H.; Geertzen, Jan H.B.; van Leeuwen, Barbara L.; Hoekstra, Harald J.; Been, Lukas B.
Abstract : Background: Despite multimodality limb salvage treatment (LST) for locally advanced extremity soft tissue sarcoma (ESTS), some patients still need an amputation. Indications for amputation and oncological outcome for these patients are described. Methods: Between 1996 and 2016, all patients who underwent an amputation for ESTS were included. Patients who underwent an amputation as primary or as non‐primary treatment formed Group I and II, respectively. Results: Thirty‐nine patients were included, 16 in Group I (41%) and 23 in Group II (59%). Tumor size or local recurrence which could not be treated with LST were the two main reasons for amputation. Local recurrence free survival (LRFS) ( P = 0.396), distant metastases free survival (DMFS) ( P = 0.965), disease‐specific survival (DSS) ( P = 0.745), and overall survival (OS) ( P = 0.718) were comparable for both groups. Ten‐year LRFS was 90.0% versus 83.7%; DMFS was 31.0% versus 42.2%; DSS was 52.2% versus 44.1%; and OS was 44.2% versus 41.6%, for group I and II respectively. Conclusions: Oncological outcome seems to be comparable between patients who underwent a primary or a non‐primary amputation for ESTS. With the on‐going possibilities concerning prosthesis and rehabilitation programs, it remains important to decide in a multidisciplinary sarcoma team meeting which treatment suits best for each individual patient.